Degradation status and deathly factor for coral death reefs in Co To islands - Cu, Nguyen Duc; Ngai, Nguyen Dang; Anh Tuyet, Dao Thi; Thao, Nguyen Van (Academia Journal of Biology, 2012)
﻿Co To Islands hold a particularly important position in political situation and marine economic development of the Northern part of the Vietnam Sea. In the past time, the Islands has a developed coral reef with over 70 species of hard corals, a high degree of coral coverage a rich reef community with 133 species of reef fishes, 17 species of crustaceans and many other species of mollusks. However, the exploitation of aquatic resources in these islands at recent time 2002-2006 years using destructive technical measures, especially cyanide chemicals has heavily reduced the biodiversity and natural resources in these islands. The survey results urgently realized in 2006 by NDAREP, ICUN, IMRE and RIMF ﻿showed that coral reefs were seriously damaged. Coverage of alive coral ferociously being from 60 to 80%, in some localities nearly 100%, has been reduced to 10 - 15%, evenly below 5%. According to the results of a survey on the environment status in Co To islands recently carried out in 2007-2009 years, the environmental conditions there at present times are completely including hychological, nutrient and pesticicles cyanide factors. Other mechanical damaged factors as mine fishing, storms are also eliminated. Therefore, the deathly factors that caused the degradation and death for coral reefs in Co To inlands that must be the fishing using cyanide toxic chemicals during recent time 2002-2006.